2014
DOI: 10.1111/1756-185x.12452
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble toll‐like receptor 2: a novel biomarker for systemic lupus erythematosus disease activity and lupus‐related cardiovascular dysfunction

Abstract: Serum sTLR2 can attenuate disease activity and negatively impact left ventricular diastolic dysfunction and hypercholersterelemia in SLE patients. Statins, corticosteroids and chloroquine increase sTLR2 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
4
20
0
1
Order By: Relevance
“…We report, for the first time, that serum sTLR2 levels are significantly elevated in MS patients compared to match HC (Figure 1 A). This is consistent with observations of increased serum sTLR2 in a number of other inflammatory diseases and disease models, including severe bacterial infection ( 38 ), experimental human endotoxemia ( 32 ), and the autoimmune disease systemic lupus erythematosus, where it serves as a biomarker of disease activity ( 29 ). Notably, sTLR2 can act as a decoy microbial receptor since it retains the capacity to bind with the PAMPs as well as TLR2 coreceptor CD14, thereby preventing surface TLR2 to bind with CD14 and PAMPs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We report, for the first time, that serum sTLR2 levels are significantly elevated in MS patients compared to match HC (Figure 1 A). This is consistent with observations of increased serum sTLR2 in a number of other inflammatory diseases and disease models, including severe bacterial infection ( 38 ), experimental human endotoxemia ( 32 ), and the autoimmune disease systemic lupus erythematosus, where it serves as a biomarker of disease activity ( 29 ). Notably, sTLR2 can act as a decoy microbial receptor since it retains the capacity to bind with the PAMPs as well as TLR2 coreceptor CD14, thereby preventing surface TLR2 to bind with CD14 and PAMPs.…”
Section: Discussionsupporting
confidence: 90%
“…As it has been reported that serum sTLR2 is a biomarker of recent infection, and of disease activity in other conditions, we measured sTLR2 levels in serum samples from MS patients in relapse and remission and compared them with those from HC ( 29 , 30 ). We observed significantly higher levels of sTLR2 in the serum samples of MS patients both during relapse (0.87 ng/ml) and remission (0.85 ng/ml) when compared with HC (0.58 ng/ml) (Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…They are capable of ligand (PAMPs and DAMPs) binding, but do not transmit the signal downstream [ 2 ]. Elevated serum levels of sTLR4 are associated with infection, predominately with bacterial, while decreased levels of sTLR2 are associated with autoimmune diseases [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that a novel observation revealed by Houssen et al, is the negative correlation between serum soluble TLR2 (sTLR2) levels and SELDAI score in SLE patients. This negative correlation was attributed to the role of sTLR2 in down regulation of TLR2 signaling through various mechanisms [23].…”
Section: Discussionmentioning
confidence: 99%